Review on the monograph of doctor of economics, professor Pavlova O. and doctor of economics, associate professor Pavlov K. on the topic: «Formation and regulation of competitive relations on the regional housing markets of Ukraine (Economic journal of Lesya Ukrainka Volyn National University, 2019)
The authors evaluated the competitive advantages and specific characteristics of their formation with the subsequent functioning of housing markets in the regions of the state, as well as the activities of construction organizations-developers within their borders. In the present situation, there is a need for regulation of competitive relations in the regional housing markets in Ukraine and the provision of transparent conditions for the market turning on them of residential properties.
Keywords: competitive advantages, housing markets, state regulation